Reproductive Performance and Culling Rate of Purebred Holstein Cows and Their Crosses With Fleckvieh and Brown Swiss Cows Under Subtropical Conditions - Nasr, Mohammed A. F.; Hussein, Mohamed A.; Alkhedaide, Adel Q.; El-Tarabany, Mahmoud S.; Roushdy, ELshimaa M. (Frontiers in Veterinary Science, 2021)
This study aimed to elucidate the reproductive performance of purebred Holstein (HO) cows with their crosses with Fleckvieh (FV) and Brown Swiss (BS) cows under subtropical conditions. A total of 677 cows (487 HO, 104 HO X FV (HFV); 50% FV and 50% HO and 86 HO X BS (HB); 50% BS and 50% HO) were enrolled in this study. Pure HO cows had significantly greater service per conception (S/C; 3.69), days open (147.9 days) and calving interval (449.6 days), than the HFV (2.89, 116.7 days and 407.4 days, respectively) and HB (3.07, 134.3 days and 434.2 days, respectively) crossbreds cows. At day 28, the conception percentage was significantly greater among HFV crossbred cows versus pure HO cows (crude odds ratios (COR) = 2.16), but embryonic loss, abortion percentage, calving difficulty, and retained placenta percentage were similar (P > 0.05) among pure HO cows and their crosses. HFV crossbreds had significantly lower incidence of endometritis (COR = 0.70, P = 0.035), mastitis (COR = 0.69, P = 0.015), and ketosis (COR = 0.53, P = 0.004) versus other cows. HB and pure HO cows had a similar incidence of mastitis, lameness, and ketosis (COR = 0.76, 0.75, and 0.81; P = 0.223, 0.468, and 0.492, respectively). HFV crossbred cows had a lower risk of culling rate than HB crossbred cows. In summary, HFV cows demonstrated the best reproductive performance in terms of S/C, days open, calving interval, conception at 28 days, mastitis percentage, ketosis percentage, and endometritis.